Four new species of Pomphopsilla Jałoszyński in Rwanda, Burundi and DR Congo (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2021)
The cephenniine genus Pomphopsilla currently comprises seven nominal species distributed in Kenya, DR Congo and the Seychelles. Four new species are described: P. punctata sp. n. (Rwanda), P. cyanguguana sp. n. (Rwanda), P. kivuana sp. n. (DR Congo), and P. burundiana sp. n. (Burundi). Key characters of each species are illustrated, and the distribution of Pomphopsilla is summarized.